A new form of familial ataxia, deafness, and mental retardation. Issue 8 (August 1993) - Reardon, W; Wilson, J; Cavanagh, N; Baraitser, M
Abstract : Conditions causing familial ataxia, deafness, and developmental delay are considered in the context of describing brothers with a new disorder characterised by these clinical features.